Bone haemangioma: case report - Folgado Alberto, Sara (2007)
The authors report a clinical case of a black woman, aged 51, obese, with hypertension and ischaemic heart disease, who was hospitalized for intense, persistent retrosternal pain. An acute coronary syndrome was excluded and further investigation revealed an expansive bone lesion in the right rib (5 cm x 4 cm x 3.5 cm), with vertebral extensions. The lesion was ill-defined, had lytic and blastic components and was associated with an increase in the adjacent soft tissues. A well delimited tumour was extracted and histological analysis revealed a haemangioma. Abdominal CT showed abnormal findings suggestive of haemangioma in the right femur, which were later confirmed using osteoarticular radiography and tomography.